Estudo comparativo do impacto ambiental do jeans CO/PET convencional e de jeans reciclado - Luciana dos Santos Duarte (2013)
Jeans is a core product in human culture, dressing one third of the world population. Being a material of a fashion product, the jeans obeys the logic of planned obsolescence which has been questioned by the current paradigm of sustainability. Aiming at reducing the environmental impact, fiber jeans mixed cotton and recycled polyester have been offered as an environmentally sustainable alternative compared to CO/PET conventional jeans. Both jeans are evaluated in this study, as the environmental impact in textile production, as well as the durability of its materials. To evaluate the durability of jeans were conducted physical tests of resistance to elongation and tensile strength; tear resistance; and pilling, according to NBR 11912, ASTM D 2261-11 and ISO 12945-1, respectively. It was also evaluated two prototypes of pants, with each type of jeans, subjected to intensive use and washes for 30 days each. Regarding the results obtained, the environmental impact assessment showed that the production of jeans with recycled fiber consumes fewer resources, such as water, energy and chemical inputs than the production of conventional jeans. In turn, mechanical strength tests and use test showed that the CO/PET recycled jeans has less durability than the jeans made by conventional manufacturing. The materials and prototypes evaluated were contextualized in scenarios of sustainability and fashion, concluding that the jeans with recycled fibers is suitable for hyper technological scenario and fast fashion, while the conventional jeans is appropriate for the scenario of slow fashion and hyper culture.